2014
DOI: 10.1186/preaccept-1506796653138778
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, risk factors and genotyping of Toxoplasma gondii in domestic geese ( Anser domestica ) in tropical China

Abstract: Background: Little information is available about the seroprevalence of Toxoplasma gondii infection in geese (Anser domestica) in China. In the present investigation, the seroprevalence, risk factors and genotyping of T. gondii in geese were investigated in Hainan province, tropical China. Findings: A total of 600 serum samples and 150 brain tissue samples were collected from six administrative regions in tropical China, and assayed for T. gondii antibodies by Indirect Haemagglutination (IHA) test. Genomic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results showed that ducks 1<years≤2 of age (OR: 4.1; 95% CI: 1.0-17.2) had four times higher risk of being positive compared with ducks ≤1 year-old, indicating that age may be a risk factor for T. gondii infection, in agreement with previous studies (40)(41)(42)(43). Age is widely considered as a risk factor for high infection rates of T. gondii (44,45).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that ducks 1<years≤2 of age (OR: 4.1; 95% CI: 1.0-17.2) had four times higher risk of being positive compared with ducks ≤1 year-old, indicating that age may be a risk factor for T. gondii infection, in agreement with previous studies (40)(41)(42)(43). Age is widely considered as a risk factor for high infection rates of T. gondii (44,45).…”
Section: Discussionsupporting
confidence: 88%
“…Age is widely considered as a risk factor for high infection rates of T. gondii (44,45). This might be attributed to increased frequency of exposure to the infectious T. gondii oocysts or the cumulative effect of the time period during which an animal can be exposed to the parasite (43,46). The present study also showed that female ducks (OR: 3.1; 95% CI: 1.3-7.4) had three times higher risk of acquiring T. gondii infection compared with male ducks, suggesting that female ducks are more susceptible to T. gondii than male ducks (47).…”
Section: Discussionmentioning
confidence: 99%
“…in Brazil. In Europe, seroprevalence ranges from 4.8%-43% (BARTOVÁ et al, 2009;MAKSIMOV et al, 2011;SANDSTRÖM et al, 2013) and from 4.7%-17% in Asia (MURAO et al, 2008;YAN et al, 2011;YANG et al, 2012;RONG et al, 2014). Geese populations from these studies comprised wild, domestic, and hunted animals.…”
Section: Discussionmentioning
confidence: 99%
“…Several serological tests have been employed to detect antibodies to T. gondii in anseriformes, such as enzyme-linked immunosorbent assay (ELISA) (MURAO et al, 2008;MAKSIMOV et al, 2011;IBRAHIM et al, 2018), direct agglutination test (DAT) (PRESTRUD et al, 2007), indirect hemagglutination (IHA) (HARFOUSH & TAHOON, 2010;RONG et al, 2014;NUNES, 2016), and modified agglutination test (MAT) (YANG et al, 2012;MANCIANTI et al, 2013;SANDSTRÖM et al, 2013;VERMA et al, 2016). However, there is still disagreement regarding the ideal method for detecting antibodies due to the variability of antigenic proteins, as well as differences in the sensitivity, and quality of commercial kits (SANTOS, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Limited information on T . gondii genotypes has been reported in patients, pets, food animals, poultry, birds and several species of wild animals [3,1216]. The genotype ToxoDB#9 is predominant in different parts of China.…”
Section: Introductionmentioning
confidence: 99%